Mind, Language and Thinking in Samuel Beckett's Waiting for Godot - Singh, Raj Kishor (Khwopa Journal, 2023)
This paper claims that mind, language and thinking have triangular relationship. It raises an issue whether language is necessary in the process of thinking. It is very debatable issue whether language and thinking are interdependent or independent elements. Role of the mind must be significant in the process of thinking. Language is a tool for thinking. This triangular issue of mind, language and thinking has been brought into the scene when Lucky, in Samuel Beckett’s play Waiting for Godot, is sitting and thinking. Lucky’s thinking inspires us to explore the triangular issue. After analysis of the data and the language used in thinking by Lucky, it is discovered that mind is a catalyst and language and thoughts are substances in the mind. Benjamin Lee Whorf's hypothesis states that the influence of language on thinking is obligatory. Oscar Wilde remarks that language is the parent, and not the child, of thought. Bertrand Russell claims the role of language is to make possible thoughts which cannot exist without it but processing is in the mind as inner or mental speech. Language influences our thinking and, thereby, our thoughts.